A newly recorded genus and twelve newly recorded species of ferns for Vietnam from Lang Biang Plateau - Chen, Cheng-Wei; Hsu, Tian-Chuan; Chao, Yi-Shan; Lu, Ping-Fong; Li, Chia-Wei; Tram, Nguyen Khanh Trinh; Nguyen, Ich Le Phuoc Thanh; Dang, Minh Tri; Luu, Hong Truong; Parris, Barbara (Phytotaxa, 2020)
One genus (Chrysogrammitis) and twelve species (Asplenium pifongiae, Chrysogrammitis musgraviana, Crepidomanes makinoi, Ctenitis sinii, Ctenopterella khaoluangensis, Didymoglossum wallii, Dryopteris hendersonii, Hymenophyllum palmatifidum, H. paniculiflorum, Polystichum prionolepis, Pteris latipinna, and Stegnogramma wilfordii) of ferns are reported as new records for Vietnam based on newly collected specimens from Lang Biang Plateau. We provide photographs of key characters, type information, voucher specimens, distribution, ecology, and notes for each newly recorded species.